LOVE ILLUMINATING THROUGH A PHOTOGHRAPHY EXHIBITION IN STELLLA MATUTINA - Siswanto, Mikael Adi; Andini, Andini; Yuliantini , Dewi (UIN Sunan Kalijaga Yogyakarta, 2025)
This article discusses the role of photography as a medium for proclaiming the values ​​of love in the Catholic faith through an exhibition entitled Stella Matutina: Love One Another, organized by the Diocese of Bandung. This exhibition presents the works of 33 photographers who reflect the message of Christian love inspired by the Gospel of John 15:12 in the form of simple and touching visual narratives. This research uses a qualitative narrative approach with a study of theological aesthetics and visual communication theories, as well as an analysis of the creative process, photography techniques, and the spiritual impact of the works exhibited. The results of the study show that the photography in this exhibition successfully proclaims Catholic values ​​in a contextual and communicative manner. Through a human interest approach and reflective visual compositions such as the use of eye-level perspectives, monochromatic colors, and natural lighting, the message of love is presented in everyday life and can be accepted across religions and cultures. Art becomes a means of preaching that does not only convey dogma, but also brings to life the experience of faith and opens up a space for inclusive spiritual encounters. This exhibition emphasizes that art, when combined with religious values, can build a civilization of love and become a reflective vehicle in a multicultural society. Keywords: Photography, Love, Proclamation of Faith, Catholic Values, Religious Visualization, Interfaith Dialogue Artikel ini membahas peran seni fotografi sebagai media pewartaan nilai-nilai kasih dalam iman Katolik melalui pameran bertajuk Stella Matutina: Kasihilah Seorang Akan yang Lain yang diselenggarakan oleh Keuskupan Bandung. Pameran ini menampilkan karya 33 fotografer yang merefleksikan pesan kasih Kristiani berdasarkan inspirasi Injil Yohanes 15:12 dalam bentuk narasi visual yang sederhana dan menyentuh. Penelitian ini menggunakan pendekatan kualitatif naratif dengan telaah teori estetika teologis dan komunikasi visual, serta analisis terhadap proses kreatif, teknik fotografi, dan dampak spiritual dari karya-karya yang dipamerkan. Hasil kajian menunjukkan bahwa seni fotografi dalam pameran ini berhasil mewartakan nilai-nilai Katolik secara kontekstual dan komunikatif. Melalui pendekatan human interest dan komposisi visual yang reflektif seperti penggunaan sudut pandang eye-level, warna monokromatik, dan pencahayaan natural pesan kasih dihadirkan dalam kehidupan sehari-hari dan dapat diterima secara lintas agama dan budaya. Seni menjadi sarana pewartaan yang tidak hanya menyampaikan dogma, tetapi menghidupkan pengalaman iman dan membuka ruang perjumpaan spiritual yang inklusif. Pameran ini menegaskan bahwa seni, ketika dipadukan dengan nilai-nilai agama, dapat membangun peradaban kasih dan menjadi wahana reflektif dalam masyarakat multikultural. Kata Kunci : Seni Fotografi, Kasih, Pewartaan Iman, Nilai Katolik, Visualisasi Agama, Dialog Lintas Iman